Cosmopolitan Archeologies - Meskell, Lynn (Duke University Press, 2009)
This book delves into the politics of contemporary archaeology in an increasingly complex international environment. Describing various forms of cosmopolitan engagement, the contributors explore the implications of applying the cosmopolitan ideals of obligation to others and respect for cultural difference to archaeological practice, showing that those ethics increasingly demand the rethinking of research agendas. While cosmopolitan archaeologies must be practiced in contextually specific ways, what unites and defines them is archaeologists' acceptance of responsibility for the repercussions of their projects, as well as their undertaking of heritage practices attentive to the concerns of the living communities with whom they work. These concerns may require archaeologists to address the impact of war, the political and economic depredations of past regimes, the livelihoods of those living near archaeological sites, or the incursions of transnational companies and institutions.